Aprendizagem docente no ensino superior: processos formativos de professores e estudantes nas licenciaturas da área de ciências biológicas, exatas e da terra - Sandri, Vanessa (2017)
This study is part of the research, Training, Knowledge and Professional Development line of the Post-Graduate Program in Education of the Federal University of Santa Maria (UFSM) and is linked to a larger research entitled "Learning of Teaching: Formative processes of students and trainers of higher education (2012 to 2016)", developed by the Research Group Teacher Training and Educational Practices: Basic and Higher Education (RGTTEP). In this research we seek to understand the formative processes and their implication in the teaching learning of trainers and undergraduate students in the area of Biological, exact and earth Sciences of a Public Higher Education Institution. As specific objectives we highlight: to know the formative trajectory of trainers and students of the degree courses in the area of biological, exact and earth sciences; To recognize the teaching conceptions of the trainers and the students of the mentioned undergraduate courses and to identify the implications of the formative processes in the teaching learning of the trainers and students of the licentiate courses in the area of biological, exact and earth sciences. In order to do it so, the methodological approach used was of a qualitative nature and developed from the sociocultural perspective of a narrative perspective based on Bolzan's studies (2001 to 2016), substantiated by Vygotsky's historical-cultural theory (1995, 2007), enunciation in Bakhtin (2011) and Clandinine Connelly(1995) and Freitas‟s narrative studies(1998, 2010). Initially, the data were collected with a questionnaire, to map and meet the trainers who work in these courses and define the choice of these subjects. Further, semi-structured interviews were conducted with twenty teachers and twenty four students who are in different stages of the undergraduate courses. We construct the analytical dynamics of our research based on the studies of the Umbrella Project, taking as central category teacher learning and the dimension of formative architecture, amplifying in two dimensions: formative trajectory and conception of teaching and a transversal element that perpasses all research processes Training. The carried-out research allowed us to understand that teacher learning is influenced by the experiences and marks produced by the personal and professional trajectory of each subject. Self and interformative actions are mobilized by the demands and needs of pedagogical work, establishing the study, the search for intellectual deepening to produce reflections and assign meanings to the construction of teaching. We emphasize that teacher learning depends on the conceptions that each subject has about teaching and these are being matured, others refuted and, consequently, intensify in the course of the training paths experienced in the degree. We also show the indispensable need to review the curricula of the investigated undergraduate courses, in order to overcome a content-oriented training aimed at research, establishing a collaborative culture in undergraduate courses. Therefore, the reflections on the set of narratives of this study allow us to understand that Students and trainers make sense of teaching when they recognize the formative processes by which they have lived, subjecting their experiences in the context of the profession, in interpersonal relations, in the formative actions and by recognizing themselves in permanent learning.